Lipoprotein biosynthesis as a target for anti-Wolbachia treatment of filarial nematodes - Johnston, Kelly L (BioMed Central, 2010)
BACKGROUND: Lymphatic filariasis and onchocerciasis are debilitating diseases caused by filarial nematodes. Disease pathogenesis is induced by inflammatory responses following the death of the parasite. Wolbachia endosymbionts of filariae are potent inducers of innate and adaptive inflammation and bacterial lipoproteins have been identified as the ligands that bind toll-like receptors (TLR) 2 and TLR6. Lipoproteins are important structural and functional components of bacteria and therefore enzymes involved in Wolbachia lipoprotein biosynthesis are potential chemotherapeutic targets. RESULTS: Globomycin, a signal peptidase II (LspA) inhibitor, has activity against Gram-negative bacteria and a putative lspA gene has been identified from the Wolbachia genome of Brugia malayi (wBm). The amino acids required for function are strictly conserved and functionality was verified by complementation tests in a temperature-sensitive Escherichia coli lspA mutant. Also, transformation of wild type E. coli with Wolbachia lspA conferred significant globomycin resistance. A cell-based screen has been developed utilizing a Wolbachia-containing Aedes albopictus cell line to assay novel compounds active against Wolbachia. Globomycin was screened using this assay, which resulted in a dose-dependent reduction in Wolbachia load. Furthermore, globomycin was also effective in reducing the motility and viability of adult B. malayi in vitro. CONCLUSIONS: These studies validate lipoprotein biosynthesis as a target in an organism for which no genetic tools are available. Further studies to evaluate drugs targeting this pathway are underway as part of the A-WOL drug discovery and development program.